Sosialisasi Pencegahan Kanker dan Stunting melalui Penyuluhan di Desa Tetei Lanan Kabupaten Barito Selatan - Nina; Restu; Yeyen; yemima; Pratama, Andreas; Setiawan, Devid; Glorianismus, Filoshopia Yasni; Bastiawan, Muhammad; Edwie, Muhammad; Amelianti, Ni Made Peby; Indrawati, Nurafny; Andarista, Oppy; Lisvigo, Silvanus; Ayu, Tantri (NAWASENA : JOURNAL OF COMMUNITY SERVICE, 2024)
Cancer and stunting are two major health problems in Indonesia, especially in rural areas with limited health access and lack of public knowledge, demanding adequate counselling and education. Thus, the role of students as agents of change is very important to increase community knowledge about stunting prevention and early detection of cancer. Through discussion methods and hands-on examples, the outreach programme in Tetei Lanan Village showed effectiveness in preventing stunting and cervical and breast cancer by improving the community's understanding of nutrition, vaccinations, and routine check-ups. Although faced with constraints such as limited internet access and health services, approaches such as direct counselling and strengthening the role of health cadres have successfully overcome these challenges. Continued support, improved access to healthcare, as well as financial assistance proved essential to achieving optimal results and strengthening awareness and prevention efforts in the community. The service programme in Tetei Lanan Village successfully raised awareness about stunting prevention and cervical and breast cancer through counselling, with a focus on nutritious food and early detection.